Sarcoidosis-associated small fiber neuropathy in a large cohort: Clinical aspects and response to IVIG and anti-TNF alpha treatment. (May 2017) - Tavee, Jinny O.; Karwa, Karen; Ahmed, Zubair; Thompson, Nicolas; Parambil, Joseph; Culver, Daniel A.
Abstract: Objective: Small fiber neuropathy commonly affects patients with sarcoidosis and is often refractory to standard immunosuppressive therapies used for systemic disease. The clinical features of sarcoidosis-associated small fiber neuropathy (SSFN) and its response to medical therapy have not been described in a large population. Methods: We performed a retrospective review of patients with SSFN seen at the Cleveland Clinic over a 4-year period. Results: SSFN was identified in 143 individuals although other causes of neuropathy were found in 28 cases. Of the remaining 115 patients, 100 (87%) were Caucasian and 72 (63%) were female. Median age at reported neuropathy onset was 46 years (range 19–77 years), while median age of systemic diagnosis was 41 years. Pain and paresthesias were the most common symptoms, of which 54% were nonlength-dependent. Dysautonomia was seen in 61 patients with cardiac symptoms (orthostasis, palpitations) as the most common presentation followed by gastrointestinal and sweating dysfunction. Symptomatic improvement with treatment was seen in 47 of 62 patients that received IVIG, 8 of 12 patients that received anti-TNF and 10 of 14 patients who received combination therapy. Of 27 patients who were untreated, 4 improved. Conclusions: The most common presentation of SSFN in our series was a painful non-length dependent polyneuropathy with the highest overall incidence in Caucasian females. In most patients, neuropathy symptoms developed within 3 years of systemic sarcoidosis diagnosis. IVIG appeared beneficial in treating SSFN symptoms while nearly 2/3 of subjects also responded favorably to anti-TNF with or without IVIG. Further prospective studies are needed. Highlights: Most common presentation of SSFN was a painful non-length dependent polyneuropathy. Highest overall incidence of SSFN was seen in Caucasian females. IVIG and anti-TNF alpha agents appeared beneficial in treating SSFN symptoms. Screening for other neuropathy causes revealed another etiology in 20% of patients.